Drivers of Socially Responsible Investing: A Case Study of Four Nordic Countries - Scholtens, Bert (Journal of business ethics, 2013)
In this study, we try to establish what determines the substantial differences in the Nordic countries’ size and composition of socially responsible investing (SRI). We investigate if these differences between Denmark, Finland, Norway, and Sweden can be associated with key characteristics in economics, finance, culture, and institutions. We find that in particular economic openness, the size of the pension industry, and cultural values of masculinity (femininity) and uncertainty avoidance can be associated with the differences in SRI in the four countries. On basis of these findings, we lay foundations for an international theory of SRI.